Geomechanical characterization for tunnels in carbonate rock masses withdissolution processes – UASD Tunnel Case (Dominican Republic) - Matencio Quispe, Herman (2025)
The study addresses the challenge of geomechanical characterization of carbonate rocks affected by dissolution and karstification, which are notadequately assessed using conventional classification methods. These methods focus on structures such as joints and fractures, overlooking specificfeatures of carbonate rocks, such as cavities. Thus, the main objective of the research is to evaluate the geomechanical characteristics of rockmasses affected by dissolution in order to establish a suitable geomechanical classification. The methodology used was descriptive, based on structured observation through detailed geological mapping, geomechanical assessments, laboratory tests, and borehole logging.Various lithotypes and their geomechanical behavior were evaluated, considering factors such as strength, weathering, rock mass structure, and cavity characteristics (shape, size, infill, moisture, and alteration). Initially, conventional classification systems were applied: RMR (Bieniawski, 1989) and GSI (Marinos & Hoek, 2000). Results showed that Coral Limestone I exhibits good geomechanical behavior, Coral Limestones II and II-A show intermediate behavior, Rock Caliche types 1 and 2 are not suitable for support, and cavities and alterations negatively impact tunnel stability.Theproposed methodology was validated during the excavation and construction of the UASD Tunnel in the Dominican Republic, yielding satisfactoryresults.